Eastern Caribbean Currency Union: selected issues (IMF WashingtonUS, 2009)
Explores the impact of U.S. business cycles on ECCU economies and questions whether even an optimal level of international reserves is adequate. Examines the emergence of unregulated investment schemes in the region and their potential economic and institutional damage. Assesses exchange rate competitiveness in the ECCU. Finds that for all but two countries in the region, fiscal policy does not react adequately to past debt accumulation to satisfy a condition for debt sustainability. Examines the vulnerability of public finance to the risk of natural disasters.
Keywords: ECONOMIC CONDITIONS